Donkey milk-derived exosomes protect against UVB irradiation-induced ferroptosis in skin cells: in vitro and in vivo evidence - Yu, Jie; Cheng, Jie; Liu, Guangyuan; Cheng, Zhijie; Niu, Pengxiang; Xu, Derui; Pei, Xinyun; Tie, Hang; Wang, Cong (Frontiers in Pharmacology, 2026)
UVB irradiation can induce ferroptosis and accelerates skin photoaging. However, the role of donkey milk-derived exosomes (DM-Exos) on UVB induced ferroptosis was unclear. In this study, using HaCaT keratinocytes and CCC-ESF-1 fibroblasts exposed to UVB irradiation (60–100 mJ/cm2), we found that UVB irradiation significantly reduced skin cell viability, while DM-Exos treatment effectively reversed this decline. To investigate the underlying mechanism, we assessed key markers of ferroptosis, including ROS, lipid peroxides (LipoROS), malondialdehyde (MDA), glutathione (GSH), 4-hydroxynonenal (4-HNE), glutathione peroxidase 4 (GPX4), and ferritin heavy chain 1 (FTH1) and the results showed that UVB irradiation increased the levels of ferroptosis-related biomarkers. DM-Exos treatment reversed these changes, suggesting its role in mitigating ferroptosis. Furthermore, in a UVB-induced photoaging mouse model, subcutaneous administration of DM-Exos ameliorated skin damage, improved hydration, and reduced ferroptosis biomarkers in dorsal skin. These findings establish DM-Exos as a novel biological agent against UVB-induced skin injury and delineate a previously unrecognized mechanism linking milk-derived exosomes to ferroptosis regulation.